PENERAPAN HUKUM TERMODINAMIKA PERTAMA DALAM PENGGUNAAN ENERGI PANEL SURYA TERHADAP PENERANGAN JALAN UMUM (PJU) - Rieke Nur Fitria; Pramudya Aulia Fadila; Hanin; Qurrotul A’yunin Nafi’ah; Avina Putri Syahida; Sapti Puspitarini (Jurnal Reflektif, 2026)
In general, street lights that use solar power are converted to electricity. The conversion of solar heat into electrical energy that causes the street lights to turn on uses the principles of the First Law of Thermodynamics. This article aims to identify the process and challenges in applying the First Law of Thermodynamics to renewable energy technologies, especially in the context of using solar energy for street lighting. The method applied is Literature Review from various journals both at national and international levels. The first law of thermodynamics is related to the creation of renewable energy which is currently the focus of efforts to create sustainable energy. This topic discusses the concept of the first law of thermodynamics, and the mechanism of converting sunlight into electrical energy and then into street lighting. Various challenges are affected in the form of heat management, the use of environmentally unfriendly materials in solar panels, expensive investment costs, energy conversion efficiency. This article reinforces the importance of applying the first law of thermodynamics to the development of renewable energy, and the challenges resolved in its implementation.